Avaliação do efeito de novos tiazólicos em dermatófitos e o uso de Tenebrio molitor como modelo de infecção - Ana Carolina Costa Menezes (2024)
Dermatophytosis is a cutaneous mycosis caused by dermatophyte fungi, named according to the site of infection (Tinea corporis, Tinea capitis and Tinea pedis). These fungi are classified into three genera: Trichophyton, Microsporum and Epidermophyton, depending on the morphology of the conidia. Furthermore, species are divided into geophilic, zoophilic and anthropophilic, depending on their natural habitat. The virulence factors of keratinolytic fungi are associated with the secretion of enzymes such as proteases and lipases that act across a broad pH spectrum and on different substrates. The treatment of dermatophytosis is based on antifungal medications for topical and systemic use, used in combination or not, belonging to the classes of allylamines, polyenes, azoles and echinocandins. The resistance mechanisms that stimulate the search for new therapeutic agents involve the overexpression of efflux pumps, mutations in target genes, activation of signaling pathways in response to stress and cellular detoxification enzymes. Infection models for studying pathogenicity and new drugs for dermatophytes are still a challenge, especially for anthropophilic species. Thus, the objective of this study was to analyze the action of new thiazole compounds against dermatophytes, followed by the evaluation and standardization of an alternative infection model using the invertebrate Tenebrio molitor for dermatophytes. The development of this model of infection with T. molitor larvae by dermatophytes will allow the study of the virulence of dermatophyte strains, through the analysis of larvae survival, as well as testing the action of new compounds. The aim is to evaluate the activity of 53 new thiazole compounds against dermatophytes, through analysis of their fungicidal and/or fungistatic activity, in vitro testing of nail fragments and exoskeleton of T. molitor, action on biofilms and production of species reactive oxygen (ROS) and peroxynitrite (PRN). Therefore, this work brings new perspectives to the treatment of dermatophytosis, and also contributes to the development of strategies to study and to evaluate the pathogenicity and new compounds that act on dermatophytes.